Manganese and rhenium-catalyzed selective reduction of esters to aldehydes with hydrosilanes. Issue 78 (1st September 2020) - Wei, Duo; Buhaibeh, Ruqaya; Canac, Yves; Sortais, Jean-Baptiste
Abstract : The selective reduction of carboxylic esters into silyl alkyl acetals promoted by manganese and rhenium catalysts provides facile access to aldehydes upon hydrolysis. Abstract : The selective reduction of esters to aldehydes, via the formation of stable alkyl silyl acetals, was, for the first time, achieved with both manganese, –Mn2 (CO)10 – and rhenium –Re2 (CO)10 – catalysts in the presence of triethylsilane as reductant. These two methods provide a direct access to a large variety of aliphatic and aromatic alkyl silyl acetals (30 examples) and to the corresponding aldehydes (13 examples) upon hydrolysis. The reactions proceeded in excellent yields and high selectivity at room temperature under photo-irradiation conditions (LED, 365 nm, 40 W, 9 h).